2009
DOI: 10.1061/(asce)1090-0268(2009)13:2(66)
|View full text |Cite
|
Sign up to set email alerts
|

Durability of GFRP Reinforcing Bars Embedded in Moist Concrete

Abstract: This paper presents mechanical, microstructural, and physical characterization of glass fiber-reinforced polymer ͑GFRP͒ bars exposed to concrete environment. GFRP bars were embedded in concrete and exposed to tap water at 23, 40, and 50°C to accelerate the effect of the concrete environment. The measured tensile strengths of the bars before and after exposure were considered as a measure of the durability performance of the specimens and were used for long-term properties prediction based on the Arrhenius theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
67
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(88 citation statements)
references
References 9 publications
10
67
0
1
Order By: Relevance
“…As expected, a more rapid reduction in the tensile strength is observed in the case of immersion in 60 ∘ C alkaline solution than in the case of immersion in 40 ∘ C alkaline solution. Comparing the present test results with those of Robert et al [16], in which the rebar is made of the same resin type and immersed into alkaline solution maintained with identical temperature level, the tensile strength of the bare bars is similar to that of the mortar-wrapped bars until 120 immersion days. However, the mortar-wrapped bar retains about 90% of its original tensile strength until 240 immersion days; on the contrary, the tensile strength of the bare bars is drastically decreased to 30% of the original strength until 300 immersion days.…”
Section: Alkaline Solution Effects Without Exposure To High Temperatusupporting
confidence: 69%
See 2 more Smart Citations
“…As expected, a more rapid reduction in the tensile strength is observed in the case of immersion in 60 ∘ C alkaline solution than in the case of immersion in 40 ∘ C alkaline solution. Comparing the present test results with those of Robert et al [16], in which the rebar is made of the same resin type and immersed into alkaline solution maintained with identical temperature level, the tensile strength of the bare bars is similar to that of the mortar-wrapped bars until 120 immersion days. However, the mortar-wrapped bar retains about 90% of its original tensile strength until 240 immersion days; on the contrary, the tensile strength of the bare bars is drastically decreased to 30% of the original strength until 300 immersion days.…”
Section: Alkaline Solution Effects Without Exposure To High Temperatusupporting
confidence: 69%
“…The results of accelerated aging test for the "Ref" specimen are compared with those reported in previous works [13][14][15][16]. As shown in Figure 7, the tensile strength of the GFPR bar specimens is very similar until 100 immersion days, compared to test results of Chen et al [15].…”
Section: Alkaline Solution Effects Without Exposure To High Temperatumentioning
confidence: 51%
See 1 more Smart Citation
“…Researches have been conducted to evaluate the durability performance in aggressive environment and to develop models for predicting long-term strength retention of GFRP bars embedded in concrete (Benmokrane et al 2002;Chen et al 2006;Robert et al 2009;Mufti et al 2007). GFRP bars were proved to be a durable face to the concrete environment and it was shown that the service lifetime allowed to reach tensile strength retention of less than 50% should be infinite (Robert et al 2009;CSA S6-06 2006) which also supported the findings of Mufti et al (2007) who tested few GFRP reinforced structures after up to 9 years in service conditions. However, it is also reported that the GFRP bars do deteriorate over time when embedded in concrete or when immersed in concrete pore solutions due to chemical reactions (Kim et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were all focused on evaluating tensile strength of GFRP bars under artificial simulated concrete pore solution, which is different from the actual concrete alkaline environmental condition. Besides, some scholars pointed out that the traditional accelerated aging in alkaline solution is too severe and prematurely degrades the GFRP bars [8][9][10][11][12]. The paper presents the actual concrete environment influence on tensile properties of GFRP bars.…”
Section: Introductionmentioning
confidence: 99%